2019
DOI: 10.1128/jb.00064-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caulobacter Cell Surface Structures in Colonization of the Air-Liquid Interface

Abstract: In aquatic environments, Caulobacter spp. can be found at the boundary between liquid and air known as the neuston. I report an approach to study temporal features of Caulobacter crescentus colonization and pellicle biofilm development at the air-liquid interface and have defined the role of cell surface structures in this process. At this interface, C. crescentus initially forms a monolayer of cells bearing a surface adhesin known as the holdfast. When excised from the liquid surface, this monolayer strongly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 95 publications
2
16
0
Order By: Relevance
“…Holdfast-mediated adherence to solid surfaces is permanent [911]. The holdfast enables cell attachment to a variety of chemically diverse materials [12], and also facilitates partitioning of cells to the air-liquid interface in aqueous media [13]. C .…”
Section: Introductionmentioning
confidence: 99%
“…Holdfast-mediated adherence to solid surfaces is permanent [911]. The holdfast enables cell attachment to a variety of chemically diverse materials [12], and also facilitates partitioning of cells to the air-liquid interface in aqueous media [13]. C .…”
Section: Introductionmentioning
confidence: 99%
“…Swarmer cells differentiate into stalked cells, whereupon they can secrete a unipolar polysaccharide adhesin known as the holdfast [5][6][7][8] (Fig 1A). Holdfast mediated adherence to solid surfaces is permanent [9][10][11]; the holdfast enables cell attachment to a variety of chemically diverse materials [12], and facilitates partitioning of cells to the air-liquid interface in aqueous medium [13]. C. crescentus tightly regulates holdfast synthesis and thus the transition between a planktonic and a surface-attached lifestyle, which likely reduces the probability of becoming restricted to a sub-optimal environment.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that temperature amongst other environmental conditions indicative of the two different environments may play a role in determining the type of biofilm formed. In Salmonella , curli is responsible for the switch [68] whereas, in C. crescentus, biofilm is initially formed as a monolayer of cells that subsequently develop into a three-dimensional structure and as the biofilm matures, it becomes more cohesive and less adherent [69]. Previous studies have confirmed that some pellicles of some organisms are composed of eDNA with close cell contact [23], sucrose, and proteins [70].…”
Section: Discussionmentioning
confidence: 99%